Host-Directed Therapies for Tuberculosis - Venketaraman, Vishwanath (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
TB is considered as one of the oldest documented infectious diseases in the world and is believed to be the leading cause of mortality due to a single infectious agent. Mtb, the causative agent responsible for TB, continues to afflict millions of people worldwide. Furthermore, one-third of the entire world's population has latent TB. Consequently, there has been a worldwide effort to eradicate and limit the spread of Mtb through the use of antibiotics. However, management of TB is becoming more challenging with the emergence of drug-resistant and multi-drug resistant strains of Mtb. Furthermore, when administered, many of the anti-TB drugs commonly present severe complications and side effects. Novel approaches to enhance the host immune responses to completely eradicate Mtb infection are urgently needed. This Special Issue will therefore cover most recent advances in the area of host-directed therapies for TB.